Microeconomic Gasoline Consumption Anomalies in Mexico: 1997-2007 - Fullerton Jr, Thomas M; Salazar, Jorge Ibarra; Elizalde, Mario (Asian Economic and Financial Review, 2015)
Economic expansion in Mexico has caused fuel consumption to increase. Because Mexico does not have sufficient refinery capacity, over 40 percent of total gasoline consumed is imported. This has implications for the balance of payments. In this paper, gasoline demand is empirically examined using cointegration and error correction approaches. The sample period utilized contains a complete business cycle, but does not include the atypical 2008 financial market collapse downturn. Results indicate that long-run equilibrium in the Mexican gasoline market may not exist during the sample period in question. This is potentially attributable to the regulatory regime that governs energy markets in Mexico. Regulated price adjustments that are not consistent with prevailing market conditions run the risk of misallocating resources. Effective gasoline subsidies currently cost Mexico several billion dollars per year. Permitting greater flexibility in private gasoline retail markets may prove beneficial in Mexico. Parameter estimates indicate that gasoline is a normal good. More provocatively, the demand curve for gasoline is found to be upward sloping. That implies that, over the course of the sample period analyzed, the income effect exceeds the substitution effect. Given recent policy changes in Mexico, the latter outcome is not expected to persist.